Energy Storage in the Emerging Era of Smart Grids 2011
DOI: 10.5772/20798
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Optimal Matrix Converter Control for a Dynamic Voltage Restorer with Flywheel Energy Storage

Abstract: This paper presents a predictive optimal matrix converter controller for a flywheel energy storage system used as Dynamic Voltage Restorer (DVR). The flywheel energy storage device is based on a steel seamless tube mounted as a vertical axis flywheel to store kinetic energy. The motor/generator is a Permanent Magnet Synchronous Machine driven by the AC-AC Matrix Converter. The matrix control method uses a discrete-time model of the converter system to predict the expected values of the input and output current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…with q * s = 0, in order to have a unity power factor on the input side. Finally, (17) and (18) are combined into a single so-called cost function…”
Section: Pcc With Reactive Power Minimisationmentioning
confidence: 99%
See 1 more Smart Citation
“…with q * s = 0, in order to have a unity power factor on the input side. Finally, (17) and (18) are combined into a single so-called cost function…”
Section: Pcc With Reactive Power Minimisationmentioning
confidence: 99%
“…Recent research has indicated the potential of model predictive control (MPC) techniques to monitor and reduce the high processing power required by microprocessors in many power electronics applications [17]. Predictive current control (PCC) can be described as a particular instance of MPC that takes into account the inherent discrete nature of the power converter using its switching states or voltage vectors and digital implementation [8,[17][18][19][20]. Several PCC methods used in MCs take into consideration the output current regulation and the reactive power minimisation on the source side, resulting in source currents that are instantaneously in phase with their respective phase voltage [8,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…PCC and PTC. Other implementations, such as predictive voltage control [39, 40, 43, 44] and predictive reactive/active power control [20, 41] can be found in the literature as well, but they are not analysed in detail here. Moreover, other variations have been presented which cannot be directly included in the classifications of Fig.…”
Section: Different Predictive Control Variations Applied To Mcsmentioning
confidence: 99%
“…Several research works, such as [22, 29–33, 37, 38, 40, 43, 45, 53, 59, 60], have discussed controlling this converter with an MPC scheme for a wide range of industrial areas including motor drive and grid‐connected applications. This control scheme contributes several advantages to the DMC.…”
Section: Mpc Contributions To Different MC Configurationsmentioning
confidence: 99%
See 1 more Smart Citation